Preferensi Masyarakat dalam Memilih Alat Transportasi Kereta Api Indonesia - Silviana Bilqis Elvin Zulvani; Pardiman Pardiman; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to: 1. Explain which attribute combinations influence people's preferences when choosing a rail transportation. 2. Describe which transportation attributes are important to the community when choosing a rail transportation means. 3. Explain what level of transportation attributes are most important to the community when choosing a Rail transportation means. The sampling technique used is a non-probability sampling technique and the data obtained are 96 respondents. The data analysis technique used in this research is conjoint analysis. The results of the study show that: 1. The combination of attributes that are considered the most important are air-conditioned carriage facilities, the price has promo tickets, the privilege is very suitable for families, the quality of ticket services can be purchased online, and the safety of no hawkers. 2. Attributes based on importance are carriage facilities, price, privileges, service quality, and safety. 3. The most important attribute level is that the price includes promo tickets, the quality of ticket services can be purchased online, the carriage facilities with air-conditioned rooms, the privilege is very suitable for families, and the safety of no hawkers. Keyword: Price, Quality of Service, Carriage Facilities, Privilege, Security.